Village Officials’ Competence in Digital-Based Services Using E-Office in Mekarwangi Village, Sumedang Regency - Nangameka, Teresa Irmina; M P, Hilmy Rahayu; Rahman, Aditya (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
The implementation of new applications to support organizational work, integral to the adoption of SPBE in Indonesia, often encounters a lack of readiness among management officials. This challenge extends to the village level, the lowest tier of government, where the introduction of the E-office as a digital-based administrative service represents both a breakthrough and a formidable hurdle for village officials unfamiliar with information technology. This study aims to assess the competence of the village officials in facilitating the operationalization of the E-office and proposes strategies to enhance their digital service proficiency, focusing on Mekarwangi Village in Tomo District, Sumedang Regency. Employing a descriptive qualitative research approach, data collection involves interviews, observations, and documentation, with data triangulation as the analytical technique. The study reveals that the competence of the Mekarwangi Village officials is currently minimal, primarily due to a lack of adequate education, training, and insufficient support from local or central governments in providing facilities for enhancing the officials' competence in managing village potential data—a critical aspect of E-office operations. In response, the Sumedang government is actively addressing this issue by regularly conducting training and socialization programs on online-based services, specifically the village E-office, for village officials and communities. Efforts have been made to improve the quality and quantity of supporting infrastructure, such as internet network capabilities and the availability of laptops. To foster competitiveness among villages, the government is also instituting awards for those successfully implementing the E-office, accompanied by guidance for villages facing challenges in its optimal operation.